(untitled) (Colombia Medica, 2021)
Trauma damage control seeks to limit life-threatening bleeding. Sequential diagnostic and therapeutic approaches are the current standard. Hybrid Room have reduced hemostasis time by integrating different specialties and technologies. Hybrid Rooms seek to control bleeding in an operating room equipped with specialized personnel and advanced technology including angiography, tomography, eFAST, radiography, endoscopy, infusers, cell retrievers, REBOA, etc. Trauma Hybrid Service is a concept that describes a vertical work scheme that begins with the activation of Trauma Code when admitting a severely injured patient, initiating a continuous resuscitation process led by the trauma surgeon who guides transfer to imaging, angiography and surgery rooms according to the patient’s condition and the need for specific interventions. Hybrid rooms integrate different diagnostic and therapeutic tools in one same room, reducing the attention time and increasing all interventions effectiveness.